2019
DOI: 10.1038/s41467-019-13634-z
|View full text |Cite
|
Sign up to set email alerts
|

The visual word form area (VWFA) is part of both language and attention circuitry

Abstract: While predominant models of visual word form area (VWFA) function argue for its specific role in decoding written language, other accounts propose a more general role of VWFA in complex visual processing. However, a comprehensive examination of structural and functional VWFA circuits and their relationship to behavior has been missing. Here, using high-resolution multimodal imaging data from a large Human Connectome Project cohort (N = 313), we demonstrate robust patterns of VWFA connectivity with both canonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
107
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 80 publications
13
107
1
1
Order By: Relevance
“…the FFA. Consistent with previous studies in adults that compared VWFA connectivity to adjacent regions 19,31,45 , we restricted our analyses to the left hemisphere in order to eliminate potential confounds of cross-hemispheric differences. The development of functional specificity in right vs. left visual cortex remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…the FFA. Consistent with previous studies in adults that compared VWFA connectivity to adjacent regions 19,31,45 , we restricted our analyses to the left hemisphere in order to eliminate potential confounds of cross-hemispheric differences. The development of functional specificity in right vs. left visual cortex remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Like in other studies, applying region of interest analyses to specifically examine the activation pattern of the visual word form area yielded focal print-sensitive activation differences between groups. Connectivity studies show, that the VWFA development 13 , 29 , and its function are largely constrained and predicted by its privileged connectivity to various areas within the (temporal) language network but also its tight coupling to the dorsal fronto-parietal attention network 51 , 83 , 84 . Such connectivity findings suggest that the VWFA activation is tuned by input from higher order language areas and attentional processes, depending also on the task requirements, the reading strategy and experience of the children.…”
Section: Discussionmentioning
confidence: 99%
“…The extended connectivity of the left vOT thus seems a prerequisite for guiding the emerging specialization in the VWFA 13 which is initiated within the first months of formal reading acquisition through the learning of letter and speech sound associations in alphabetic languages 26 , 27 , 29 , 33 , 85 , 86 . In addition the strong structural and functional link of the VWFA to the attentional system 51 , 87 , 88 may support the guidance of visual attention by amplifying the representations of words and fostering subsequent phonological and lexical processing 51 . Impairments in attentional mechanisms in dyslexia may cause poor orthographic representations 89 and phonological decoding deficits 90 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The left fusiform gyrus, including the visual word form area (VWFA) and surrounding cortex, has long been implicated in the processing of visual words (Glezer et al, 2009;Dehaene and Cohen, 2011;Hirshorn et al, 2016). This so-called "visual word form system" (VWFS) involves VWFA and is inherently coupled with the higher-order language system at both functional and structural levels (Stevens et al, 2017;Chen et al, 2019). Meanwhile, previous studies have shown that activation in this area is correlated with phonological awareness, suggesting that when processing print, this area is automatically involved -even if no explicit phonological processing is required -in the phonological coding system (Frost et al, 2009;Price and Devlin, 2011;Pugh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%